2012
DOI: 10.1371/journal.pone.0030248
|View full text |Cite
|
Sign up to set email alerts
|

Massage Therapy for Osteoarthritis of the Knee: A Randomized Dose-Finding Trial

Abstract: BackgroundIn a previous trial of massage for osteoarthritis (OA) of the knee, we demonstrated feasibility, safety and possible efficacy, with benefits that persisted at least 8 weeks beyond treatment termination.MethodsWe performed a RCT to identify the optimal dose of massage within an 8-week treatment regimen and to further examine durability of response. Participants were 125 adults with OA of the knee, randomized to one of four 8-week regimens of a standardized Swedish massage regimen (30 or 60 min weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
2
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 61 publications
2
85
2
4
Order By: Relevance
“…While the prevalence of neck and low-back pain were comparable between the 2 generations, the baby boomers were more likely to report head and facial pain. Several nonpharmacological interventions, such as acupuncture, 33 tai chi, 34 yoga, 35 and massage, 36 have shown evidence in managing chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…While the prevalence of neck and low-back pain were comparable between the 2 generations, the baby boomers were more likely to report head and facial pain. Several nonpharmacological interventions, such as acupuncture, 33 tai chi, 34 yoga, 35 and massage, 36 have shown evidence in managing chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…In response to this demand, the center of gravity of massage therapy studies has moved from basic efficacy trials to more translational research, testing detailed dosing protocols to optimize clinical outcomes for specific conditions [34]. One barrier to progressing along this translational pathway to realworld conditions is developing effective payment models that include massage therapy, allowing access to more people who suffer from chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Two features of massage therapy that are aligned with these current national recommendations are: 1) its low side-effect profile and 2) its capacity to simultaneously treat co-morbid conditions such as chronic pain and anxiety. Massage therapy has minimal side-effects, moderate cost, and has been shown to be effective for anxiety [19][20][21][22][23][24][25][26] as well as chronic back, neck, and knee pain due to OA [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In 2 small studies, Haas et al 30,31 found greater improvement for back pain and cervicogenic headache among patients who received 3 or 4 chiropractic treatments per week for 3 weeks than among those receiving fewer treatment per week. In a 5-arm, 8-week trial of massage for persons with osteoarthritis, Perlman et al 32 found that 60 minutes of weekly or twice weekly massage was clearly superior to usual care and appeared better than 30 minutes of twice weekly massage.…”
Section: Discussionmentioning
confidence: 99%